Mixed epithelial stromal tumor of the kidney (MESTK): Case Report. - ammari, bassam; muheilan, muheilan; Khatatbeh, hassan; Ayyad, Malik; Qsus, Tareq; Obeidat, Fatima (Jordan Medical Journal, 2016)
INTRODUCTION: Mixed epithelial stromal tumor of the kidney (MESTK) is a newly introduced and rare kidney tumor subtype; to our knowledge approximately 100 cases have been reported. CASE PRESENTATION: We report a case of MESTK with detailed clinicopathological findings, presented to emergency department with gross hematuria and clot retention managed by radical nephrectomy. DISCUSSION: Although MESTK are benign, they cannot be distinguished from other malignant neoplasms until after nephrectomy due to lack of any typical radiological features. They can cause serious sequelae; including gross hematuria and serious drop in hemoglobin as the case we present here shows. This is why it is important to early diagnose and treat this condition. CONCLUSION: This case highlights the importance of early introduction of imaging in patients presenting with gross hematuria. Failure to diagnose this lesion as the underlying cause of hematuria may have led to recurrence and malignant transformation.